A case report of high-grade astroblastoma in a young adult - Bhalerao, Sagar (CNS Oncol, 2019)
Astroblastoma is an uncommon neuroepithelial primary tumor of the brain which is of uncertain origin. We present a case of high-grade astroblastoma in an 18-year-old female with a severe headache, loss of appetite, vomiting and generalized weakness. The patient had undergone a right frontoparietal craniotomy. Large subfalcine meningioma was excised. The lesion was suspected to be a meningioma. Primary radiological investigation revealed a 6.8 cm × 5.8 cm × 5.4 cm lesion. Although the radiological and intraoperative findings were of an extra-axial tumor, the histology and immunophenotype was of an astroblastoma. The patient was treated with cyclophosphamide, cisplatin and etoposide chemotherapy regimen. The patient was later treated with bi-weekly bevacizumab. The patient had improved symptomatically post-chemotherapy. However, there was no significant difference in lesion size. The patient died after 2 weeks. The prognosis of patients with astroblastoma is extremely poor as observed in our case.